Pembelajaran dan Pengaplikasian Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa Sekolah Dasar Negeri Klabang 3 Guna Mewujudkan Gemilang (Generasi Maju, Inovatif, dan Cemerlang) - Adhitya Wardhono; Ciplis Gema Qori’ah; Bhim Prakoso; M Abd Nasir; Agung Nugroho Puspito; Rumaisya Aatikah Ruskaya; Arifah Zahra Dhamargita; Lintang Wulan Rika Efendi; Del Viera Alphi Nur Syahara; Amalia Nurul Inayah; Fa’iz Salsabila Dwina Feiyanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Clean and Healthy Living Behavior (PHBS) teaching activities at Klabang 3 State Elementary School aim to increase students' awareness of the importance of maintaining health. Through four meetings with 28 students, this activity included education on how to wash hands properly, keep nails clean, and recognize dangerous food ingredients. The methods used include demonstrations, experiments, and interactive discussions, allowing students to understand and apply the material in everyday life. The evaluation results show a significant increase in students' knowledge and behavior regarding PHBS. This project also aims to overcome the low PHBS coverage in Indonesia which currently only reaches 35.8%, far from the national target of 70%. By involving students in remote areas such as Klabang, it is hoped that this activity can create agents of change in the school and community environment. Through a fun, educational approach, it is hoped that students will not only understand the basic principles of a healthy lifestyle but also be able to apply them consistently in everyday life. It is hoped that this activity can form a younger generation that is healthier and ready to face future challenges.